ANALISIS IMPLEMENTASI ASUHAN KEBIDANAN KOMPLEMENTER DENGAN TINGKAT KEPUASAN IBU MELAHIRKAN - Rofikatul Mufidah; Solichatin; Setiawandari, Setiawandari (Rena Cipta Mandiri, 2025)
Maternal satisfaction is an important indicator of the quality of midwifery services. Complementary midwifery care is believed to improve mothers’ comfort and satisfaction. This study aimed to analyze the relationship between the implementation of complementary midwifery care and the level of maternal satisfaction at independent midwifery practices (TPMB) in the South Surabaya area. The study used a cross-sectional design involving 25 midwives and 25 postpartum mothers. Data were obtained through observation and questionnaires and analyzed using the Spearman Rank test. The results showed that most midwives implemented complementary care in the good category (56%), while only 24% of mothers felt very satisfied. There was a significant relationship between the implementation of complementary care and maternal satisfaction (p=0.000; r=0.764). It is concluded that improving the quality and consistency of complementary midwifery services can enhanc.